2012
DOI: 10.1158/0008-5472.can-11-3760
|View full text |Cite
|
Sign up to set email alerts
|

MET Signaling Regulates Glioblastoma Stem Cells

Abstract: Glioblastomas multiforme (GBM) contain highly tumorigenic, self-renewing populations of stem/initiating cells [glioblastoma stem cells (GSC)] that contribute to tumor propagation and treatment resistance. However, our knowledge of the specific signaling pathways that regulate GSCs is limited. The MET tyrosine kinase is known to stimulate the survival, proliferation, and invasion of various cancers including GBM. Here, we identified a distinct fraction of cells expressing a high level of MET in human primary GB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
146
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 48 publications
7
146
0
1
Order By: Relevance
“…[29][30][31] EGFR, MET, PDGFR, and miRNAs have been implicated in the regulation of GSC functions. [32][33][34][35][36][37][38][39][40] This study identifies for the first time miR-134 as a critical RTK-regulated tumor suppressive hub that targets KRAS and STAT5B and mediates RTK and RTK inhibitor effects on GBM malignancy.…”
mentioning
confidence: 89%
“…[29][30][31] EGFR, MET, PDGFR, and miRNAs have been implicated in the regulation of GSC functions. [32][33][34][35][36][37][38][39][40] This study identifies for the first time miR-134 as a critical RTK-regulated tumor suppressive hub that targets KRAS and STAT5B and mediates RTK and RTK inhibitor effects on GBM malignancy.…”
mentioning
confidence: 89%
“…In accordance with these observations, we detected an upregulation of signaling through MET in the HGG-02 cells, which may partially compensate for the downregulation of EGFR signaling caused by the loss of EGFR gene copy. MET overexpression has been associated with a shorter survival time and poor response (20), and it has been suggested that MET activation is required for the acquisition of the glioblastoma cancer stem cell phenotype (21). Furthermore, upregulated phosphorylation of RON, the MSP receptor, may indicate another compensatory mechanism in HGG-02 cells.…”
Section: Discussionmentioning
confidence: 99%
“…120 In fact, inhibition of c-Met signaling in GBM stem cells disrupts tumor growth and invasiveness both in vivo and in vitro. 95 Attempts at EGFR inhibition in GBM often induce high levels of c-Met activation as a mechanism of anti-EGFR resistance, further potentiating c-Met as a therapeutic target. 96 Inhibition of c-Met expression using chimeric transgenes decreases GBM tumor growth and malignancy, 2 including decreased angiogenesis as well as increased apoptosis in vivo.…”
Section: C-mesenchymal-epithelial Transitionmentioning
confidence: 99%